ABSURDITAS ALBERT CAMUS DALAM NOVEL TERJEMAHAN KARYA ZURIYATI MENCARI PEREMPUAN YANG HILANG - Ari Khairurrijal Fahmi (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract:  The aim of this study is to describe depthly about  an Albert Camus Absurdity in a translation novel by Prof Zuriyati "Mencari Perempuan yang  Hilang". The focus of this research is an expressions and words in the novel which have elements of life uncertainty, feelings of turmoil, and death in Albert Camus's concept. This study uses the Content Analysis method with expressions in the form of sentences as data derived from the novel book " Mencari Perempuan yang  Hilang " as a data source. The researcher noted several patterns of expressions found in the novel in the form of uncertainty in life, fluctuations in feelings, to feelings of desire to commit suicide which are manifestations of albert camus's absurdity in real life. Key Words: (Absurdity; Albert Camus; Novel; Mencari Perempuan yang hilang).